PRODUCTION OF Eucalyptus urophylla x Eucalyptus grandis SEEDLINGS WITH DIFFERENT FERTILIZERS - Camara, Rodrigo; Silva, Cristiane Figueira da; Pereira, Marcos Gervasio; Alves, Gabriela Cavalcanti; Ferreira, Dereck Halley Anthony Alves; Melo, Lucas Amaral de (Floresta, 2020)
Mineral fertilization is an important practice that contributes to the production of seedlings with satisfactory quality. This study aimed to evaluate the effect of the application of potassium chloride (KCl) and monoammonium phosphate (MAP) on growth and nutrition of Eucalyptus urophylla x Eucalyptus grandis seedlings. The experiment was conducted in full sun, with direct sowing in tubes containing composite substrate (Pinus bark, coconut fiber, bovine manure and vermiculite). The experimental design was a randomized block design in a 5 x 2 factorial scheme, with five doses of KCl (0.0, 0.025, 0.050, 0.100, and 0.200 g seedling-1) and two doses of MAP (0 and 0.10g seedling-1), with four replicates. At 120 days, the effect of the interaction between the KCl and MAP doses was verified for the variables: diameter at root collar, dry mass of the aerial part (DMAP) and total (TDM), Dickson Quality Index, N content, P K in the aerial part, K content in the roots, absorption efficiency (AE) of N and P. For the variables: height (H); leaf area; root dry mass (RDM); H/DRC and DMPA/RDM ratios; and N and P content in the roots, only effect of the application of MAP is observed, whereas for AE_K the effect was only of KCl. Thus, there is variation in the effect of KCl doses as a function of morphological and nutritional variables evaluated. In general, the best seedling growth and nutrition occurs with the applied dose of 0.100 g KCl + 0.10 g MAP seedling -1.